Pengaruh Locus Of Control, Turnover Intention, Komitmen Organisasi Dan Kecerdasan Emosional Spiritual Quotient (Esq) Terhadap Dysfunctional Audit Behavior - Yulastri Herliza; Mia Angelina Setiawan (Universitas Negeri Padang, 2019)
Dysfunctional audit behavior is the behavior of auditors in the audit process that is not appropriate or deviates from the standards set. The aim of the study was to determine: (1) the influence of locus of control on dysfuncional audit behavior, (2) the effect of turnover intention on audit behavior dysfuncional, (3) the influence of organizational commitment on dysfuncional audit behavior, (4) the influence of emotional, spiritual, quetiont intelligence (ESQ) against dysfuncional audit behavior.This research was conducted at the Republic of Indonesia BPK Representative auditor West Sumatra Province in 2019. The samples obtained were 44 auditors. The sample collection method uses total sampling technique. The data analysis technique used is multiple linear regression. The results showed (1) locus of control did not affect the dysfunctional audit behavior with a significance value of 0.012 <0.05, (2) turnover intention had a positive effect on dysfunctional audit behavior with a significance value of 0.003 <0.05 (3) organizational commitment had no effect towards dysfunctional audit behavior with a significance value of 0.249> 0.05 and (4) emostional spiritual quotient does not affect the bahaviour dysfunctional audit with a significance value of 0.716> 0.05.